Plasma Periostin and Delayed Cerebral Ischemia After Aneurysmal Subarachnoid Hemorrhage - Kanamaru, Hideki (Neurotherapeutics, 2019)
Delayed cerebral ischemia (DCI) is a serious complication of aneurysmal subarachnoid hemorrhage (SAH). Matricellular protein periostin (POSTN) has been found to be upregulated and linked with early brain injury after experimental SAH. The aim of the present study was to investigate the relationship between plasma POSTN levels and various clinical factors including serum levels of C-reactive protein (CRP), an inflammatory marker, in 109 consecutive SAH patients whose POSTN levels were measured at days 1–12 after aneurysmal obliteration. DCI developed in 16 patients associated with higher incidence of angiographic vasospasm, cerebral infarction, and 90-day worse outcomes. POSTN levels peaked at days 4–6 before DCI development. Cerebrospinal fluid (CSF) drainage was associated with reduced POSTN levels, but did not influence CRP levels. There was no correlation between POSTN levels and other treatments or CRP levels. To predict DCI development, receiver-operating characteristic curves indicated that the most reasonable cutoff POSTN levels were obtained at days 1–3 in patients without CSF drainage (80.5 ng/ml; specificity, 77.6%; sensitivity, 85.7%). Multivariate analyses using variables obtained by day 3 revealed that POSTN level was an independent predictor of DCI. POSTN levels over the cutoff value were associated with higher incidence of DCI, but not angiographic vasospasm. This study shows for the first time that CSF drainage may reduce plasma POSTN levels, and that POSTN levels may increase prior to the development of DCI with and without vasospasm irrespective of systemic inflammatory reactions in clinical settings. These findings suggest POSTN as a new therapeutic molecular target against post-SAH DCI. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s13311-018-00707-y) contains supplementary material, which is available to authorized users.